Cedera persendian lutut pada atlet - Roy Januardi Irawan, (Ilmu Keolahragaan, 2012)
Abstract : Knee joint is a very importantjoint in the body, because in addition to functioning as a motion whichis quite high mobility, as well as the support body weight while standing. This increases the chance for injury to the areaduring practice and competition. Injuries to the knee joint can be caused by trauma (impact), arthritis, oreveryday activities excessive, and therefore a complaint of pain in the knee of the most widely felt. Perceivedcomplaints vary, ranging from minor complaints to severe, depending on the severity of the injury. In this article will discuss the anatomy of the knee joint, knee joint injurycauses, prevention, the first aid on the injury, and post-injury orrehabilitation.